In silico and in vivo characterization of cabralealactone, solasodin and salvadorin in a rat model: potential anti-inflammatory agents - Malik A; Arooj M; Butt TT; Zahid S; Zahid F; Jafar TH; Waquar S; Gan SH; Ahmad S; Mirza MU (Dove Medical Press, 2018)
Arif Malik,1 Mahwish Arooj,2 Tariq Tahir Butt,3 Sara Zahid,4 Fatima Zahid,1 Tassadaq Hussain Jafar,1 Sulayman Waquar,1 Siew Hua Gan,5 Sarfraz Ahmad,1 Muhammad Usman Mirza6 1Institute of Molecular Biology and Biotechnology (IMBB), University of Lahore, Lahore, Pakistan; 2University College of Medicine and Dentistry (UCMD), University of Lahore, Lahore, Pakistan; 3Khawaja Muhammad Safdar Medical College, Sialkot, Pakistan; 4Faculty of Pharmacy, University of Lahore, Lahore, Pakistan; 5School of Pharmacy, Monash University Malaysia, Subang Jaya, Malaysia; 6Department of Pharmaceutical and Pharmacological Sciences, Rega Institute for Medical Research, Medicinal Chemistry, University of Leuven, Leuven, Belgium Background: The present study investigates the hepato- and DNA-protective effects of standardized extracts of Cleome brachycarpa (cabralealactone), Solanum incanum (solasodin), and Salvadora oleioides (salvadorin) in rats. Materials and methods: Hepatotoxicity was induced with intraperitoneal injection of carbon tetrachloride (CCl4) (1 mL/kg b.wt.) once a week for 12 weeks. The hepato- and DNA protective effects of the extracts in different combinations were compared with that of a standard drug Clavazin (200 mg/kg b.wt.). Tissue alanine aminotransferase, alpha-fetoprotein, tumor necrosis factor alpha (TNF-α), isoprostanes-2α, malondialdehyde, and 8-hydroxydeoxyguanosine, the significant hallmarks of oxidative stress, were studied. Results: Histopathological findings of the liver sections from the rat group which received CCl4+cabralealactone, solasodin, and salvadorin demonstrated improved centrilobular hepatocyte regeneration with moderate areas of congestion and infiltration comparable with Clavazin. For in silico study, the identified compounds were subjected to molecular docking with cyclooxygenase-2 and TNF-α followed by a molecular dynamics study, which indicated their potential as anti-inflammatory agents. Conclusion: Cabralealactone, solasodin, and salvadorin confer some hepatoprotective and DNA-damage protective effects against CCl4-induced toxicity. They successfully restored the normal architecture of hepatocytes and have the potential to be used as inhibitor to main culprits, that is, cyclooxygenase-2 and TNF-α. They can combat oxidative stress and liver injuries both as mono and combinational therapies. However, combination therapy has more ameliorating effects. Keywords: cabralealactone, solasodin, salvadorin, antioxidant, COX-2 inhibitor, anti-inflammatory